Synaptic Transmission: Looking for Clues to Autism Spectrum Disorders (ASD) Etiology in Copy Number Variants Containing Synaptic Genes - Oliveira, B.A. (2013)
Copy Number Variants (CNVs) play an important role in susceptibility to ASD, often mediated by the deletion or duplication of genes involved in synaptic structure and function. Increasing evidence suggests a central role for defects in synaptic structure and function in the pathogenesis of non-syndromic ASD. In this study we tested the hypothesis of an enrichment in CNVs encompassing synaptic transmission genes in ASD